ENHANCING STUDENTS' FICTION ANALYSIS SKILLS THROUGH QUIZIZZ MEDIA IN A PROBLEM-BASED LEARNING MODEL - Suputra, Gusti Ketut Alit; Idris, Idris; Tahir, Moh.; Syamsuddin, Syamsuddin; Gazali, Gazali; Nandi, Riri Apriana N. (JURNAL EDUSCIENCE, 2025)
Purposes—This study aims to increase students' fiction analysis by integrating Quizizz media into the Project-Based Learning model. It explores how this combination fosters engagement, critical thinking, and literary comprehension, particularly in analyzing the main elements, such as plot, theme, setting, and moral/ message.Methodology- This study used mixed-method approaches, combining quantitative analysis and test results, a questionnaire, and qualitative knowledge from interviews with the teacher. This study was conducted in SMP Negeri 4 Palu, involving 32 students from the eighth grade. The students are selected from stratified random sampling. The data-collecting instrument consisted of a fiction test analysis, a questionnaire, and a Likert scale on engagement and motivation. In contrast, a semi-structured questionnaire was given to the teachers, and an expert and statistical analysis assessment confirmed the validity and reliability of the test.Findings- Integrating quizzes in the PBL framework significantly increases the students' comprehension of fictional analysis, with an average score of 91,94%, which is categorized as high competency. The highest proficiency level score belongs to theme (100%) and morel/message (100%), meanwhile plot (84%) and characterization (81%) pose a bigger challenge. Teacher interviews highlight the variability of students' comprehension, engagement disparity, and resource accessibility problems as influencing factors. Quizizz gamified games, instant feedback, competitive quizzes, and interactive engagement were found to motivate students and improve their understanding of the literary concept.Significance—This study bridges the gap in the research by evaluating the empirical integration of gamification and PBL in literary education. This finding contributes to the pedagogical improvement of digital learning, showing how interactive and student-centered approaches can improve high-level thinking skills in fraction analysis. This study also highlights the importance of teachers' facilities, fair technology access, and strategic guidance instruments in maximizing learning outcomes,